Mplus and the R mirt Package: A Comparison of Model Parameter Estimation for Generalized Partial Credit Model (GPCM) - Al Fariz, Arif Budiman (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2024)
This article aims to carry out an empirical demonstration to calibrate data using the generalized partial credit model (GPCM) and compare the results of GPCM analysis on paid software, namely Mplus, and open-source software, namely R Package Mirt. The data used in this study used secondary data in the form of item scores from the future orientation scale or Skala orientasi masa depan (S-OMD) with a total of 326 participants using a Likert scale with 4 response options. The results of this study show that GPCM is fit for OMD scale data. Comparison of analysis results using Mplus and R Package mirt shows the same output, such as discrimination parameters and item difficulty levels. The resulting factor score correlation also has a perfect correlation or one. In conclusion, open-source software is capable of having the same computing performance as paid software, and even has several additional features that are not found in paid software.